Treatment, pathological characteristics, and prognosis of pulmonary inflammatory myofibroblastic tumor–a retrospective study of 8 cases - Zhu, Xiao; Chen, Wen-Bang; Xing, Fu-Bao; Zhou, Shao; Tang, Zhen; Li, Xiao-Jun; Zhang, Lei; Huang, Yu-Chen (Frontiers in Oncology, 2022)
Objective: Inflammatory myofibroblastic tumor (IMT) is a rare disease. We reviewed data from eight patients diagnosed with pulmonary IMT (PIMT) at our hospital with the aim of summarizing and analyzing the characteristics of PIMT to improve our understanding of the disease. Methods: From January 2012 to December 2019, eight patients underwent surgical intervention for PIMT at The First Affiliated Hospital of Bengbu Medical College. Resected tumors were subjected to pathological and immunohistochemical analyses. The follow-up duration for all patients ranged from 2 years and 3 months to 9 years and 9 months (median: 6 years and 9 months). Results: The male:female ratio was 5:3, and the mean age was 48.50 years (21–74 years). Two patients (25%) with lung disease discovered via chest computed tomography during physical examinations had not experienced any symptoms. Six patients (75%) presented at the hospital because of cough, expectoration, blood in sputum, and chest tightness. Lesions from all eight patients were surgically removed, and PIMT was confirmed based on pathological examinations and immunohistochemical results. No patient received additional treatment after discharge. All cases have been followed up to the time of writing, without any tumor recurrence or distant metastasis. Conclusion: The age of onset of PIMT is usually over 40 years, and its clinical symptoms are easily confused with those of lung cancer. PIMT can only be diagnosed by histopathology and immunohistochemistry. Complete surgical resection is the preferred treatment, as patients undergoing surgery require no additional treatment, such as chemotherapy, and the survival rate is good.